2000
DOI: 10.1007/bf01279353
|View full text |Cite
|
Sign up to set email alerts
|

Arabinogalactan protein and wall-associated kinase in a plasmalemmal reticulum with specialized vertices

Abstract: Arabinogalactan protein and wall-associated kinase (WAK) are suspected to be regulatory players at the interface between cytoplasm and cell wall. Both WAK(s) and arabinogalactan shown likely to represent arabinogalactan protein(s) have been visualized there with computational optical-sectioning microscopy. The arabinogalactan occurs in a polyhedral array at the external face of the cell membrane. WAK, and other proteins as yet unidentified, appear to fasten the membrane to the wall at vertices of the array. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 60 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…The transformants were streaked on YPDA and SD/-Leu/-His/-Trp/-Ade/X-a-Gal medium respectively. The plates were incubated at 30°C for 3 days for examination the WAK1 antibody as a probe revealed immunologically related proteins in pea (Pisum sativum), tobacco (Nicotiana tabacum) and maize (Zea mays) (He et al 1996;Gens et al 2000). Expressed sequence tags for WAK-like genes have been identified in tomato (Lycopersicon esculentum) and soybean (Glycine max).…”
Section: Discussionmentioning
confidence: 99%
“…The transformants were streaked on YPDA and SD/-Leu/-His/-Trp/-Ade/X-a-Gal medium respectively. The plates were incubated at 30°C for 3 days for examination the WAK1 antibody as a probe revealed immunologically related proteins in pea (Pisum sativum), tobacco (Nicotiana tabacum) and maize (Zea mays) (He et al 1996;Gens et al 2000). Expressed sequence tags for WAK-like genes have been identified in tomato (Lycopersicon esculentum) and soybean (Glycine max).…”
Section: Discussionmentioning
confidence: 99%
“…They could be involved in gravisensing by perceiving the deformation between the cell wall and the plasma membrane. Gens et al (2000) hypothesized the existence of an architectural organization involving WAK, arabinogalactan proteins (AGP) at the interface between cytoplasm and cell wall. Several studies also showed the upregulation of AGP in response to gravistimulation (Lafarguette et al, 2004; Azri et al, 2014).…”
Section: Identification Of Cellular and Molecular Actors In Gravisensmentioning
confidence: 99%
“…Several studies also showed the upregulation of AGP in response to gravistimulation (Lafarguette et al, 2004; Azri et al, 2014). This “plasmalemmal reticulum” could play a critical role in mechanosensing and possibly gravisensing (Gens et al, 2000). More recently, it has been shown that mechanosensitive channels including MCA2 could be also involved in gravisensing (Monshausen and Haswell, 2013; Iida et al, 2014).…”
Section: Identification Of Cellular and Molecular Actors In Gravisensmentioning
confidence: 99%
“…There is some evidence to suggest AtGRP3 could be a ligand for the WAK1 receptor (Park et al 2001). There may also be an association between AGPs and WAKs, based on the co-localisation of AGP-epitopes and WAK1 in immunofluoresence studies (Gens et al 2000). Signal inputs, arrows pointing towards the nucleus; signal outputs, arrows pointing towards wall.…”
Section: The Cell Wall-plasma Membrane-cytoskeleton Continuummentioning
confidence: 99%
“…Mounting evidence indicates that AGPs have a specific function during root formation, the promotion of somatic embryogenesis, pollen tube guidance, alternation between sporophytic and gametophytic transitions in the ovules, resistance to root-dependent transformation by Agrobacterium, hormone signalling and xylem differentiation/vascular function in Zinnia and Arabidopsis (Seifert and Roberts 2007). Physical connections between the wall and the PM were originally inferred from microscopic observations of the presence of AGPs as a fuzzy 'glycocalyx' occupying the PM-wall interface (Roberts 1990) and then as discrete connections (Hechtian strands), particularly in plasmolysed cells upon salt stress Gens et al 2000;Lamport et al 2006;Pickard 2008). Since AGPs were know to be highly water soluble protoeglycans it was unclear how they might fulfill this role.…”
Section: The Cell Wall-plasma Membrane-cytoskeleton Continuummentioning
confidence: 99%